2018
DOI: 10.1186/s12885-018-4191-2
|View full text |Cite
|
Sign up to set email alerts
|

The SBRT database initiative of the German Society for Radiation Oncology (DEGRO): patterns of care and outcome analysis of stereotactic body radiotherapy (SBRT) for liver oligometastases in 474 patients with 623 metastases

Abstract: BackgroundThe intent of this pooled analysis as part of the German society for radiation oncology (DEGRO) stereotactic body radiotherapy (SBRT) initiative was to analyze the patterns of care of SBRT for liver oligometastases and to derive factors influencing treated metastases control and overall survival in a large patient cohort.MethodsFrom 17 German and Swiss centers, data on all patients treated for liver oligometastases with SBRT since its introduction in 1997 has been collected and entered into a central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 29 publications
5
97
0
12
Order By: Relevance
“…The achieved one-year LC of 62.5% is slightly lower, while the one-year LC of 87.5% for patients with colorectal cancer is in line with the results of local control from other studies, ranging from 71 to 95% [26,27,[29][30][31]. This study showed that there was a signi cant difference in local control in patients with colorectal cancer compared to other histologies (87.5% vs 37.5%, p=0.014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The achieved one-year LC of 62.5% is slightly lower, while the one-year LC of 87.5% for patients with colorectal cancer is in line with the results of local control from other studies, ranging from 71 to 95% [26,27,[29][30][31]. This study showed that there was a signi cant difference in local control in patients with colorectal cancer compared to other histologies (87.5% vs 37.5%, p=0.014).…”
Section: Discussionsupporting
confidence: 89%
“…No signi cant difference in one-year survival was achieved between the observed groups (p=0.147). The results of other studies range from 68.6% to 83.5% [28][29][30][31]. Rusthoven et al showed that there was a group of favorable histologies, which include colorectal cancer, breast and kidney cancer, carcinoids, GIST and sarcomas, which has a signi cantly longer mean survival of 32 months compared to other adverse histologies with a mean survival of 12 months (p=0.001) [26].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, Zhao et al reported that a larger GTV volume significantly correlated with inferior LC following adrenal SBRT [41]. Similar to pulmonary and hepatic SBRT, a clear doseresponse relationship is also expected for the treatment of adrenal gland metastases [17,42]. Chance et al recently reported no local failures following adrenal SBRT with a BED 10 > 100 Gy [26].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to conventionally fractionated radiotherapy, SBRT allows for the delivery of highly conformal doses or radiation, enabling tumor ablation. While SBRT is well established and widely applied in the treatment of pulmonary and hepatic oligometastases [17][18][19][20], the literature for adrenal metastases is scarce. Predominantly small and retrospective studies exist which do not primarily focus on oligometastatic or oligoprogressive disease, but also include patients treated with palliative intent [21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of image guidance and conformal radiotherapy techniques, the treatment of both primary and secondary liver tumours has experienced significant improvement over the past few years, leading to increased local control rates and decreased normal tissue toxicity [14][15][16][17][18][19].…”
Section: Indications For Radiotherapymentioning
confidence: 99%